PEMANFAATAN TONGKOL JAGUNG MENJADI ASAP CAIR MENGGUNAKAN PROSES PIROLISIS - Martins, Olga Dasilva; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
The stench caused by the breakdown of proteins by microbes produce a shing odor that is often encountered by rubber farmers cause bokar quality ( though rubber material ) to be low and cause environmental pollution if not handled in a proper way . In the timber industry , the wood becomes easy rotten, easily attacked by termites and easily decayed , it can be said that the quality of the wood is low. Solutions to this problemâs is to utilize the technology of liquid smoke. The purpose of this study was to determine the quality and quantity of liquid smoke corncob non-food as a natural preservative that can be applied to rubber plantations and wood industries. This study begins with the cleaning process, enumeration and drying. Then weighed as much as 3 kg of corn cobs and put into a pyrolysis reactor at a temperature of 175 Â°C, for 5 hours. The third stage product analysis by GC/MS for the brand Hewlett Packard 6890 MSD 5973 GC equipped Chesstation data base system and a pH meter. The results showed that the quantity of liquid smoke corncob based on the yield is 31.65 % . The quality of liquid smoke seen from phenol content is 1, 38 % and acidity ( As. Acetate ) at 1.3 %. Keywords : Corn Cob, Pyrolisis, Condensation, Liquid Smoke